Wind Loads Guide to the Wind Load Provisions of ASCE 7-16 - Coulbourne, William L.; Stafford, T. Eric (American Society of Civil Engineers, 2020)
Wind Loads: Guide to the Wind Load Provisions of ASCE 7-16 provides a comprehensive overview of the wind load provisions in Minimum Design Loads and Associated Criteria for Buildings and Other Structures, ASCE/SEI 7-16. In this helpful guide, authors Coulbourne and Stafford focus on the provisions that affect the planning, design, and construction of buildings for residential and commercial purposes.Whereas the 2016 revision of ASCE 7 has retained the previously reorganized wind load provisions, the important changes in the ASCE 7-16 wind load provisions areModified wind speed maps for the country west of the hurricane-prone region;A fourth wind speed map for Risk Category IV structures;Revised methodology to determine exposure category;Addition of a ground elevation factor to the velocity pressure equation;New provisions for roof top solar arrays, canopies, and bins, tanks, and silos; andRevised pressure coefficients for components and cladding for sloped roofs.Wind Loads provides users with tools and insight to apply ASCE 7-16 in everyday practice. This updated guide introduces readers to the relevant sections of the standard and provides an extensive overview of the design procedures and the revised wind speed maps.This guide includes 14 chapters with 10 worked examples of real-life design problems applying the appropriate use of analytical and simplified procedures for calculating wind loads for a variety of common structure types, as well as answers to more than 30 frequently asked questions, grouped by topic.This book is an essential reference for practicing structural engineers, as it offers the most authoritative and in-depth interpretation of the wind loads section of Standard ASCE/SEI 7-16.William L. Coulbourne, P.E., is a structural engineering consultant located in Annapolis, Maryland. He is a member of the ASCE 7 Wind Load Task Committee, and he coauthored the wind loads guide to ASCE/SEI 7-05 and ASCE/SEI 7-10.T. Eric Stafford, P.E. is a structural engineering consultant located in Birmingham, Alabama. He is a member of the ASCE 7 Wind Load Task Committee, and he has coauthored Significant Changes to the Minimum Design Load Provisions of ASCE 7-16 and authored Significant Changes to the Wind Load Provisions of ASCE 7-10: An Illustrated Guide.
Keywords: Wind-pressure.; Wind resistant design.; Buildings -- Standards -- United States.; Buildings -- Aerodynamics.; Gust loads.; elektronické knihy; electronic books